Influence of financial subsidies on innovation efficiency of start-up enterprises - Zhou, Yuzhong; Wang, Liming; Ren, Hang; Wang, Lun; Zhang, Shihan; Aamir, Muhammad (Frontiers in Environmental Science, 2022)
The start-up period is the most difficult period for enterprises to survive and innovate. How will government subsidies affect the innovation efficiency of enterprises in the start-up period? And, is there any heterogeneity? The academic research is still relatively preliminary and controversial. This study adopts the cash flow method to screen a sample of start-ups from Chinese GEM, STAR Market and SME board-listed companies from 2010 to 2020 for empirical research. The study found that financial subsidies can generally promote the innovation efficiency of start-ups, but there is also significant heterogeneity by industry, region and whether the subsidies are sustainable. Financial subsidies generally have a signaling effect that facilitates startups to attract external capital, and this effect is most significant in the industrial sector. Overall, fiscal decentralization negatively regulates the effect of subsidies on the innovation efficiency of start-ups, especially in the public utilities and industrial sectors. The government subsidies are relatively insignificant to improve the innovation efficiency of start-up enterprises in non-first-tier cities, especially in small and medium-sized cities, and the multiplier effect is relatively small. The effect of non-sustainable subsidies is not significant because they cannot produce a long-term mechanism and thus are difficult to influence future expectations and decisions. The subsidy effect is not significant in other industries outside the industrial sector, and the lower the level of industry competition, the weaker the signaling effect of enterprise credit, the less conducive to its access to external innovation resources to enhance innovation efficiency through the signaling effect of government subsidies. Moreover, financial decentralization does not improve the innovation efficiency of government subsidies as expected, but weakens the innovation efficiency of fiscal subsidies for start-up enterprises in general. The study proposed that the government (especially the small and medium-sized city government) should optimize the business environment and financial capital allocation, change the supervision and management mechanism, improve the efficiency of capital utilization and reduce the crowding out effect. The government's subsidy policy should be further standardized and refined.